Membumikan ekonomi Syariah di Indonesia ( perspektif sosioyuridis) - Hamid,M. Arfin, 1967- (Jakarta : Elsas, 2006)
Islamic economic system in Indonesia from socio-juridical viewpoint
Daftar pustaka: 333-344
Keywords: Economics -- Religious aspects -- Islam; Islam -- Economic aspects -- Indonesia